Preparation and in vitro & in vivo evaluation of cephalexin matrix tablets - Boi Basanta Kumar Reddy; Kambhayathughar Eswara Venkata Nagoji; Satyanarayan Sahoo (Universidade de São Paulo, 2018)
The purpose of the study is to develop cephalexin controlled-release matrix tablets by using lower proportions of release retardant polymer and to establish their in vitro & in vivo correlation. Tablets were compressed by incorporating polymers in a matrix form along with drug which prolong the drug release. Twelve formulations were prepared by mixing ethyl cellulose (EC) and hydroxypropyl methylcellulose (HPMC) (three different viscosity grades) in various proportions. F-1 to F-4 formulations were prepared by incorporating drug, HPMC K4M and ethyl cellulose in 100 : 5 : 5, 100 : 10 : 5, 100 : 15 : 5 and 100 : 20 : 5; similarly, F-5 to F-8 were prepared with HPMC K15M; and F-9 to F-12 were prepared with HPMC K100M using a wet granulation process maintained same proportions, along with drug and EC. Tablets were evaluated for their pre-compression and post-compression characteristics and they were found to be in limits. From the dissolution testing, F-4 showed 100.34% medicament release in 12 h. In vivo studies were conducted on rabbit and pharmacokinetic parameters of the optimized formulation were evaluated using HPLC method. It was found that matrix tablets showed increased t1/2 and decreased Kel. The design signified that the drug release rate from tablets was influenced by the small proportion (around 7% of a tablet weight) of polymer mixture and it controlled 100% medicament release upto 12 h effectively with the low grade viscosity of HPMC combination, with good in vitro & in vivo correlation.